2023
DOI: 10.3389/fpubh.2023.1109446
|View full text |Cite
|
Sign up to set email alerts
|

Family context as a double-edged sword for psychological distress amid the COVID-19 pandemic with the mediating effect of individual fear and the moderating effect of household income

Abstract: BackgroundThe COVID-19 pandemic drives psychological distress. Previous studies have mostly focused on individual determinants but overlooked family factors. The present study aimed to examine the associations of individual and family factors with psychological distress, and the mediating effect of individual fear and the moderating role of household income on the above associations.MethodsWe conducted a population-based cross-sectional survey on Chinese adults in Hong Kong from February to March 2021 (N = 2,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The study found that psychological distress was more prevalent in women than in men, regardless of their family income level. This is consistent with the well-established link between financial situation and psychological distress [53]. This is in line with the global economic crisis generated by the pandemic, which has had a greater impact on women [54].…”
Section: Working Conditionssupporting
confidence: 89%
“…The study found that psychological distress was more prevalent in women than in men, regardless of their family income level. This is consistent with the well-established link between financial situation and psychological distress [53]. This is in line with the global economic crisis generated by the pandemic, which has had a greater impact on women [54].…”
Section: Working Conditionssupporting
confidence: 89%
“…Workers’ income is a conditioning variable for developing PD, and thus, the negative association between family well-being and PD was stronger among those with lower incomes. This in particular justifies exploring how inequality in family resources may affect mental health to a greater extent [ 35 , 42 ]. In this study, a family income of less than EUR 1200 or not having enough money to make ends meet was found to be associated with the development of PD.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, household income and psychological distress were found to be negatively correlated. 26 Esophageal cancer is a chronic wasting disease and is expensive to treat. Patients have no source of income during radiotherapy and recuperation, and the financial pressure on the family directly translates to psychological pressure for the patients, and it further increases their chances of suffering from depression.…”
Section: Discussionmentioning
confidence: 99%